2017
DOI: 10.1371/journal.pone.0188427
|View full text |Cite
|
Sign up to set email alerts
|

Increased soluble IL-7 receptor concentrations associate with improved IL-7 therapy outcomes in SIV-infected ART-treated Rhesus macaques

Abstract: The use of interleukin-7 (IL-7) as an immunorestorative therapeutic has proven effective in HIV infection, cancer and bone marrow transplantation. Mediating its activity through membrane-bound IL-7 receptor α (mCD127), IL-7 therapy increases T-cell numbers and survival. A soluble form, sCD127, is found in plasma, and we have previously identified increased plasma sCD127 concentrations in HIV infection. Furthermore, patients with high sCD127 exhibited the best viral control, implicating a role for IL-7 or sCD12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…However, recent data demonstrate that the bio-activity of IL-7 is directly enhanced by the presence of soluble CD127 (sCD127) (57). Indeed, the positive benefit of IL-7 therapy in SIV infected rhesus macaques was dependent on high levels of sCD127 (58). We therefore measured plasma levels of IL-7 and sCD127 in HIV-infected children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent data demonstrate that the bio-activity of IL-7 is directly enhanced by the presence of soluble CD127 (sCD127) (57). Indeed, the positive benefit of IL-7 therapy in SIV infected rhesus macaques was dependent on high levels of sCD127 (58). We therefore measured plasma levels of IL-7 and sCD127 in HIV-infected children.…”
Section: Resultsmentioning
confidence: 99%
“…However, lower levels of sCD127 have been observed by others in HIV-infected patients compared to healthy controls (89). Moreover, higher levels of sCD127 in plasma were associated with improved immune reconstitution in SIV infected rhesus macaques treated with recombinant IL-7 (58). The potentiating effect of sCD127 on IL-7 signaling is supported by mechanistic studies showing it enhances the bioactivity of IL-7 when the cytokine is limiting, as it is presumed to be the situation in-vivo (57, 59).…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of sIL-7Ra in shaping IL-7 bioavailability are complex. Several reports demonstrated that sIL-7Ra serves as a reservoir of IL-7 and hence increases its half-life due to relatively low affinity (53,60). Lundström et al provided a model for sIL-7Ra-mediated IL-7 regulation, proposing that sIL-7Ra/rhIL-7 with a very high molar ratio (>5000) may increase the bioactivity of IL-7 by stabilizing its reservoir (53).…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of sIL-7Rα in shaping IL-7 bioavailability are complex. Several reports demonstrated that sIL-7Rα serves as a reservoir of IL-7 and hence increases its half-life due to relatively low affinity ( 53 , 60 ). Lundström et al.…”
Section: Discussionmentioning
confidence: 99%
“…Rational selection of cytokines during T-cell culture, e.g. favoring IL7 and IL15 over IL2, may also aid in the generation of a more robust T-cell product [58,59]. T-cell exhaustion could also be targeted; similar to cancer patients, HIV infected individuals' T-cells express higher levels of PD1 [60,61], Tim3 [62], and other exhaustion markers.…”
Section: -Considerations For Anti-hiv Car T Cells Enabling Life-longmentioning
confidence: 99%